2020
DOI: 10.1177/2472555219873095
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl-tRNA Synthetase from Pseudomonas aeruginosa: Characterization and Identification of Inhibitory Compounds

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes nosocomial infections and has highly developed systems for acquiring resistance against numerous antibiotics. The gene ( lysS) encoding P. aeruginosa lysyl-tRNA synthetase (LysRS) was cloned and overexpressed, and the resulting protein was purified to 98% homogeneity. LysRS was kinetically evaluated, and the Km values for the interaction with lysine, adenosine triphosphate (ATP), and tRNALys were determined to be 45.5, 627, and 3.3 µM, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, there was overlap between the mutations seen in the colonies from the control arm and the colonies from the treated arms for most strains, consistent with the assumption of amplification of pre-existing resistant mutants. The aspS mutation in the PAOD1ΔmexR control colony can be considered equivalent to the lysS mutations in the treatment arms (50, 51). In PAΔmexR a commonly occurring large genomic deletion in galU caused resistance in a control mutant but was not selected by treatment because of its higher fitness cost compared to the oprD mutation which was selected by treatment (52).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was overlap between the mutations seen in the colonies from the control arm and the colonies from the treated arms for most strains, consistent with the assumption of amplification of pre-existing resistant mutants. The aspS mutation in the PAOD1ΔmexR control colony can be considered equivalent to the lysS mutations in the treatment arms (50, 51). In PAΔmexR a commonly occurring large genomic deletion in galU caused resistance in a control mutant but was not selected by treatment because of its higher fitness cost compared to the oprD mutation which was selected by treatment (52).…”
Section: Discussionmentioning
confidence: 99%
“…23 We also recently showed that bilirubin was a specific inhibitor of ATP binding LysRS. 24 In support of ATP competition specificity by these compounds in TyrRS, this same chemical compound library has been screened in our laboratory against several other aaRS enzymes (PheRS, GluRS, MetRS, GlnRS, LeuRS, LysRS, ProRS, ArgRS, AspRS, and HisRS) from P. aeruginosa , all of which have ATP as a substrate. In no instance in these screens were the TyrRS hit compounds observed to inhibit the activity of these additional aaRS enzymes.…”
Section: Discussionmentioning
confidence: 99%
“… Authors’ Note The authors disclose that portions of the Materials and Methods section were previously described in the following articles and are described here for clarity and descriptive purposes: Balboa et al, 24 Hu et al, 11 Pena et al, 12 Escamilla et al (Glutaminyl-tRNA Synthetase from Pseudomonas aeruginosa : Characterization, Structure, and Development as a Screening Platform. Protein Sci.…”
mentioning
confidence: 99%
“…Lysyl-tRNA synthetase (LysRS) has been validated as a promising target for antimalarial, anti-Cryptosporidium, anti-Pseudomonas aeruginosa, and anti-Mycobacterium tuberculosis therapies [23][24][25] . The ATP-binding pocket is the most promising area for the development of LysRS inhibitors.…”
mentioning
confidence: 99%